Feature of operation of separator with flexible cylinder for grain unmixing - V. Yu. Churyumov (Сельскохозяйственные машины и технологии)
For increase in grain production it is necessary to use effectively machines for postharvest grain handling. But their shortcoming is the unsatisfactory work of the separating tools which is not conforming to modern requirements. The research of separator with the flexible cylinder revealed that its efficiency and particles passing through throughs depend on the relative speed of a grain layer and mesh lengths. Values of relative speeds of a layer for the cylinders having throughs of various length in case of which the greatest separation of particles is possible are established. At a cylinder circumferential speed of 5.17 m per second for throughs 16 mm long the relative speed of a layer should not exceed 1.04 m per second; of 56 mm - 2.07 m per second; of 96 mm - 3.43 m per second. Fine particles separation through cylinders throughs (processing capacity) corresponds to theoretical prerequisites. The author determined angular coordinates in a material feed zone where relative speeds of a layer were high - 2.2-4.0 m per second. Processing capacity of throughs at the beginning of a zone was equal to zero, then with reduction of speed slowly increased. Throughs of bigger length in this zone (96 mm) separated approximately twice more particles, than short one(16 mm). In a zone of the main separation the relative speed of a layer decreased from 1.8 to 0.8 m per second. Processing capacity in all mashes increased. throughs of bigger length had, respectively, the best processing capacity. The greatest allocation of particles through throughs corresponds to the relative speed of a layer of 0.7-0.9 m per second. The completeness of separation equal 0.8 and above, is reached in cylinders with throughs 96 mm long for 2 operation cycles, and with a length of 16 mm - for 3 cycles. Specific throughput was equal 1.05 and 0.7 kg per second per 1 sq. m respectively. Due to operation of a separator with the flexible cylinder and throughs of 56 mm long grain separation grade reached 99.0-99.2 percent. At the same time specific throughput of a separator with the flexible cylinder is about 2.00-2.25 times higher, than in option with a flat screen.